Association between instillation time of glaucoma eye drops and their efficacy - A.M. Getmanova; A.Yu. Brezhnev; I.R. Gazizova; A.V. Kuroyedov; O.N. Onufriichuk (РМЖ "Клиническая офтальмология")
A.M. Getmanova1, A.Yu. Brezhnev2, I.R. Gazizova3, A.V. Kuroyedov4,5, O.N. Onufriichuk6 1Bryansk Regional Hospital, Bryansk, Russian Federation 2Kursk State Medical University, Kursk, Russian Federation 3Institute of Experimental Medicine of the Russian Academy of Sciences, St. Petersburg, Russian Federation 4P.V. Mandryka Military Clinical Hospital, Moscow, Russian Federation 5Pirogov Russian National Research Medical University, Moscow, Russian Federation 6G.I. Turner National Medical Research Center for Children’s Orthopedics and Trauma Surgery, Pushkin, Russian Federation Modern pharmacotherapy for glaucoma includes a wide range of intraocular pressure (IOP)-lowering medications of various groups. Yet, current set of medications cannot address a myriad of challenges in glaucoma treatment. Therefore, the search for novel pharmacotherapies for glaucoma is underway. IOP and the efficacy of topical IOP-lowering medications fluctuate throughout the day being volatile items. In the past decade, 24-hour IOP monitoring has provided novel data on 24-hour efficacy of many IOP-lowering medications. However, despite a large number and volume of studies, optimal instillation period of various glaucoma eye drops is still unclear. An interesting and promising area of modern pharmacotherapy is chronotherapy that implies target prescription of a drug in specific daytime considering circadian rhythms to achieve maximum effect. This paper reviews current modalities of personalized chronopharmacotherapy and their potential application in r outine glaucoma practice. This personalized approach will help achieve target IOP and improve glaucoma control. Keywords: intraocular pressure, 24-hour monitoring, diurnal IOP fluctuations, glaucoma, pharmacotherapy, chronotherapy. For citation: Getmanova A.M., Brezhnev A.Yu., Gazizova I.R. et al. Association between instillation time of glaucoma eye drops and their efficacy. Russian Journal of Clinical Ophthalmology. 2020;20(2):85–91. DOI: 10.32364/2311-7729-2020-20-2-85-91.